ALTRIRAS: A Computer Game for Training Children with Autism Spectrum Disorder in the Recognition of Basic Emotions. (2nd May 2019) - Almeida, Leandro M.; Silva, Diego P. da; Theodório, Daieny P.; Silva, Wolley W.; Rodrigues, Silvia Cristina M.; Scardovelli, Terigi A.; Silva, Alessandro P. da; Bissaco, Marcia Aparecida S.
Abstract : This paper presents a computer game developed to assist children with Autism Spectrum Disorder (ASD) to recognize facial expressions associated with the four basic emotions: joy, sadness, anger, and surprise. This game named ALTRIRAS is a role-playing game (RPG), a kind of game pointed out by the literature as the most suitable for these children for being more social than competitive. It has recreational settings built with 2D graphic interface to keep the children's attention and an access control and a register mechanism to allow the monitoring of the child's progress. The data collection of the functional, nonfunctional, psychological, and educational requirements, as well as the evaluation of its consistency and usability, was made by a multidisciplinary team consisting of five experts in each of the following expertises: pedagogy, psychology, psychopedagogy, and game development. The effectiveness test of the game was performed by 10 children with ASD and 28 children with neurotypical development, which were separated into control and experimental groups, respectively. All experts and children with neurotypical development answered the System Usability Scale (SUS) questionnaire after playing the game. The results were positive, between experts and volunteers regarding their acceptance. However, the time of exposure to the game in children with ASD should be increased to effective assistance in the recognition of facial expressions.